Lipofibromatous hamartoma of the median nerve with macrodactyly of middle finger - Mohammed Saeed, Mubder A. (J Clin Orthop Trauma, 2019)
Lipofibromatous Hamartoma (LFH) is a rare tumour affecting the peripheral nerves, mostly the median nerve. It is benign and slowly growing. Less than 100 cases have been reported in the literature, about one quarter of them are associated with macrodactyly in the field of the affected nerve. We reported a case of a 13 years old female with LFH of the median nerve at the level of the wrist associated Macrodactyly of the ipsilateral middle finger treated surgically by decompression only.